PENGARUH WORK-FAMILY CONFLICT DAN KEPUASAN KERJA TERHADAP KOMITMEN ORGANISASIONAL DAN TURNOVER INTENTION - Satria Utama, Dewa Gede Andika; Sintaasih, Desak Ketut (E-Jurnal Manajemen, 2015)
The study was conducted on the employees of Bank Mandiri Branch Office of Veterans. Sampling using saturated sample method. Respondents were 67 people karyawan.Data collected using a questionnaire supported method of observation and interviews. Data analysis technique used is path analysis. The results showed that (1) work-family conflict and a significant negative effect on organizational commitment. (2) job satisfaction and significant positive effect on organizational commitment. (3) work-family conflict and significant positive effect on turnover intention., (4) job satisfaction and a significant negative effect on turnover intention. (5) organizational commitment and significant negative effect on turnover intention., and (6) the effect of indirectly identifying organizational commitment is not able to reduce the level of work-family conflict influence on turnover intention , But the results of this study prove that a high level of job satisfaction coupled with organizational commitment on the employee can reduce turnover intention.
Keywords: work-family conflict, job satisfaction, organizational commitment, turnover intention